Utilização do registro de preços realizado por meio da modalidade pregão eletrônico e seu impacto nas compras governamentais - Costa, Maria Vânia Pires (2012)
This work aims to analyze the Purchasing Policy of Ceará State, using Prices Registration System. A comparison was made between auctions conducted in electronic trading without prices registration in 2006 and 2008 and bids in the same mode with prices registration in the years 2009, 2010 and 2011 to the acquisition of a wide range of goods. To analyze the effectiveness of Prices Registration procedure, we used data of similar goods acquired by public administration. In the analysis, it was used linear regression. The proposed model used three variables: purchase price, number of participants, and bidding time. We verified that price and bidding time are not relevant and that the number of participants has a significant relation to purchase price, showing that Prices Registration procedure is not a decisive factor to electronic auction effectiveness.